Interdisciplinary Science and Social Studies Education in The Context of Five Weeks in a Balloon - Müge Aygün; Yasemin Hacıoğlu; Derya Ceylan; Elif Durkan (Journal of Science Learning, 2022)
This study aims to determine the usability of the book ‘Five Weeks in a Balloon’ authored by Jules Verne, as a context for interdisciplinary teaching of fourth-grade science and social studies courses. As a document review, the book was analyzed based on the Science and Social Studies Curricula/Turkey-2018. The book was associated with all learning areas of the Science Curriculum and five of the seven learning areas of the Social Studies Curriculum. It was determined first the association between the two curricula and the book, then starting points for planning appropriate activities for multidisciplinary, interdisciplinary, and transdisciplinary teaching. As a result, the book can use as a context for fourth-grade science and social studies courses. Also be used in multidisciplinary, interdisciplinary, and transdisciplinary teaching to integrate science and social studies courses. Teachers and researchers can carry out various studies by designing interdisciplinary environments by benefiting from the study results.